Analysis of sequential dual immobilization of type I collagen and BMP-2 short peptides on hydrolyzed poly(buthylene succinate)/β-tricalcium phosphate composites for bone tissue engineering. (September 2019) - Singhatanadgit, Weerachai; Sungkhaphan, Piyarat; Theerathanagorn, Tharinee; Patntirapong, Somying; Janvikul, Wanida
Although attempts have been made to immobilize dual short peptides on a biomaterial surface, the optimization, characterization and functional analysis of the peptide immobilization onto poly(buthylene succinate)/β-tricalcium phosphate (PBSu/TCP) composites have not yet been reported. The present study was, therefore, carried out to optimize and characterize the dual immobilization of type I collagen short peptide (COLsp) and bone morphogenetic protein-2 short peptide (BMP-2sp) onto hydrolyzed PBSu/TCP (HPBSu/TCP) composites, and the bioactivity of the resulting dual peptide-immobilized surfaces was also determined in vitro. The results demonstrated that sequential immobilization of the dual short peptides was successfully established. Each of the peptides was chemically bound to the 1.5 M NaOH-treated composite (with the PBSu to TCP weight ratio of 60:40) (HPBSu/TCP-6040–1.5); bright red fluorescence of COLsp (25 µM) and vividly green fluorescence of BMP-2sp (50 µM) were individually observed explicitly on the dual peptide-immobilized material. As a result, the HPBSu/TCP-6040–1.5 composite film conjugated with both 25 µM Col I and 50 µM BMP-2 was examined for its osteogenic efficacy. The results showed that COLsp/BMP-2sp-immobilized HPBSu/TCP composite significantly enhanced hMSC proliferation as well as osteoblast differentiation of hMSCs under osteogenic induction. Most importantly, COLsp/BMP-2sp-immobilized HPBSu/TCP composite induced biomineralization in the absence of any additional osteogenic stimulus. The present study has successfully demonstrated the sequential immobilization of the dual short peptides, i.e., COLsp and BMP-2sp, on HPBSu/TCP surface, with each short peptide being chemically bound to the hydrolyzed composite surface. The COLsp/BMP-2sp-immobilized HPBSu/TCP film possessed the bioactivities of the respective full-length proteins by stimulating hMSC proliferation, osteoblast differentiation and, most importantly, mineralization without the requirement of exogenous osteogenic supplements. This suggests highly improved performance of the biologically responsive HPBSu/TCP composite and thus its potential use in bone tissue engineering.